(untitled) - Shinpo, Mitsuru (Vancouver, 1976)
This book is a product of the friendship extended to me by numerouss people. A Canada council doctoral fellowship facilitated my field research in 1969
Keywords: Agriculture,Economic development,Nông nghiệp,Phát triển kinh tế; Economic aspects,Social aspects,Khía cạnh kinh tế,Khía cạnh xã hội; Japan,Nhật Bản